Trusted Computing: Principles and Applications - Feng, Dengguo (Advances in Computer Science, 2017)
The book summarizes key concepts and theories in trusted computing, e.g., TPM, TCM, mobile modules, chain of trust, trusted software stack etc, and discusses the configuration of trusted platforms and network connections.